BEHAVIOR OF PRESTRESSED CONCRETE BEAM USING REACTIVE POWDER CONCRETE - Sumartono, Ignatius Harry; Purnomo, Heru; Purnomo, Sidiq; Murdono, Feryandy (Institut Teknologi Sepuluh Nopember, 2023)
The behavior of prestress pretension beams made of Reactive Powder Concrete (RPC) concrete with compressive strength above 120 MPa included in the Ultra High Performance Concrete (UHPC) classification was investigated to study the mechanical properties of concrete and the performance of prestressed beams against static load tests. The mechanical properties of RPC materials include concrete compressive strength, concrete tensile strength, concrete elastic modulus values and concrete density compared to 70 MPa High Strength Concrete (HSC) concrete. Curing concrete at an early age using high temperature hot steam (steam curing) ensures the development of the compressive strength of concrete. Experimental tests were carried out on 4 pretension beams designed to be used as highway bridge beams, namely beam #1 (30/50-HSC-NF-S); beam #2 (30/50-RPC-F-S); beam #3 (17/50-RPC-NF-S); beam #4 (17/50-RPC-NF-S). The mechanical properties of RPC concrete show superior values compared to HSC concrete. From the results of the static test, only beam #3 (RPC beam which does not use steel fiber in mixing) which shows a value of flexural resistance below the theoretical value due to brittle destruction that occurs in the beam. Steel fiber effectively maintains beam integrity thereby maximizing bending resistance, preventing explosive brittle destruction, and preventing concrete fragmentation during peak loads.